Potential drug?drug interactions in a medical intensive care unit of a university hospital - (:unkn) unknown (My University, 2016)
0

Background/aim: Drug drug interactions (DDIs) can impact patient safety. Occurrence of clinically important DDIs is higher for intensive care unit (ICU) patients. This observational study aimed to evaluate the potential DDIs in medical ICU patients of a university hospital. Materials and methods: The Medical Pharmacology Department organized consultation reports for ICU patients in order to detect the DDIs. To focus on clinically important DDIs, interactions in the C, D, or X risk rating categories of the Lexi-Interact online database were analyzed. Frequency and clinical risk rating categories of DDIs were detected. Relationship between number of prescriptions and DDIs were assessed. The most frequent drug/drug groups were identified. Results: Of 101 ICU patients, 45.5% were found to have DDIs. We detected 125 C (72.2%), 37 D (21.4%), and 11 X (6.4%) risk category interactions. A statistically significant increase in the number of DDIs was shown with the number of prescriptions (P = 0.002). The most frequent DDIs were between agents acting on the cardiovascular system and corticosteroids (12.8%). Conclusion: Results of this study show that pharmacological consultation plays a critical role in the recognition of DDIs for improvement of medication management and effective therapeutic endpoints without any adverse or toxic reactions.
Keywords: Cerrahi